Simple preparation method of mesoporous carbon carrier for fuel cell

By adding polysaccharides and activators to the acid solution using colloidal nanosilicon dioxide templates, mesoporous carbon support is prepared, which solves the complex problem of carbon support preparation in existing fuel cells and achieves high-efficiency and low-cost fuel cell catalysts.

CN119601692APending Publication Date: 2025-03-11XIAMEN ZIJIN NEW ENERGY & NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411766528.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The carbon carrier preparation methods used in existing fuel cells are relatively complex and it is difficult to achieve the goals of high efficiency and low cost.

Method used

Colloidal nanosilicon dioxide is used as a template, polysaccharides and activators are added to the acid solution, and the mesoporous carbon support is prepared after heating, drying, pyrolysis and graphitization.

Benefits of technology

The pore structure design of the carbon support is realized, which limits the size of platinum particles, inhibits the aging of platinum particles, improves the stability and performance of the catalyst, and reduces the amount of platinum used.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601692A_ABST
    Figure CN119601692A_ABST
Patent Text Reader

Abstract

The invention discloses a simple preparation method of a mesoporous carbon carrier for a fuel cell, which comprises the following steps: adding polysaccharide into an acid solution, and adding colloidal SiO2 nanoparticles and an activating agent while stirring to finally obtain a mixed solution; heating the mixed solution to 50 DEG C, stirring, evaporating the solvent, and drying at room temperature to obtain a semitransparent film; placing the obtained semitransparent film in a tubular furnace, heating to 900 DEG C in a nitrogen atmosphere, pyrolyzing at 900 DEG C, and then naturally cooling to room temperature to obtain a carbon carrier; soaking the carbon carrier with a hydrofluoric acid solution, and then cleaning with deionized water; and placing the treated carbon carrier in a graphitization furnace, heating to 1600 DEG C under the protection of argon, pyrolyzing at the temperature, and naturally cooling to room temperature to obtain the mesoporous carbon carrier for the fuel cell. Platinum particles of the platinum-carbon catalyst prepared from the carbon carrier are more uniform, and the stability of the carbon carrier is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of mesoporous carbon carriers used in fuel cells, and in particular to a simple preparation method of mesoporous carbon carriers used in fuel cells. Background Art

[0002] As China gradually pays more attention to the hydrogen energy industry, hydrogen fuel cells, as an important part of this large industry, have attracted the attention of major corporate research institutes. Many researchers are committed to achieving high-efficiency and low-cost development of fuel cells. The most important of these is the platinum-carbon catalyst used as the cathode material in fuel cells. Since the catalytic effect of the catalyst depends not only on the size and crystal state of the platinum particles, but also on the pore structure, particle size and pore size of the carrier, etc., the preparation of carbon carriers that meet the working scenarios of fuel cell catalysts has a great contribution to the performance of fuel cells. Through the research and development of high-performance platinum-carbon catalysts, it is possible to reduce the use of platinum while meeting performance requirements. And then realize the vision of high performance and low cost of fuel cells.

[0003] At present, many research works are in the stage of modifying carbon carriers. There are few studies on artificially designing the structure of carbon carriers and developing new carbon carriers. Therefore, a simple preparation method for carbon carriers for fuel cells is needed to achieve the goal of high efficiency and low cost of fuel cells. Summary of the invention

[0004] In view of the deficiencies of the prior art, the present invention aims to provide a simple method for preparing a mesoporous carbon carrier for a fuel cell.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] A simple method for preparing a mesoporous carbon carrier for a fuel cell comprises the following steps:

[0007] S1. Add polysaccharide to the acid solution, add colloidal SiO2 nanoparticles and activator while stirring, and finally obtain a mixed solution;

[0008] S2, heating the mixed solution obtained in step S1 to 50° C. with stirring to evaporate the solvent and then drying at room temperature to obtain a translucent film;

[0009] S3, placing the translucent film obtained in step S2 in a tube furnace, heating it to 900° C. in a nitrogen atmosphere, pyrolyzing it at 900° C., and then naturally cooling it to room temperature to obtain a carbon carrier;

[0010] S4, soaking the carbon support obtained in step S3 with a hydrofluoric acid solution, and then washing with deionized water;

[0011] S5. The cleaned carbon carrier obtained in step S4 is placed in a graphitization furnace, heated to 1600° C. under the protection of argon gas, and naturally cooled to room temperature after pyrolysis at 1600° C., thereby obtaining a mesoporous carbon carrier for a fuel cell.

[0012] Furthermore, in step S1, the acid solution includes one or more of nitric acid solution, sulfuric acid solution, acetic acid solution, perchloric acid solution, and hydrochloric acid solution.

[0013] Furthermore, in step S1, the polysaccharide is one or more of starch, cellulose, chitosan, polyfructose, and agar.

[0014] Furthermore, in step S1, the activator includes one or more of zinc chloride, calcium chloride, calcium carbonate, potassium hydroxide, and sodium hydroxide.

[0015] Furthermore, in step S1, the particle size of the colloidal SiO2 nanoparticles is 5-50 nm.

[0016] Furthermore, in step S1, 0.5-2.5 g of polysaccharide is added to 50 mL of 0.1 mol / L acid solution, and 1 g of colloidal SiO2 nanoparticles and 0.2-0.4 g of activator are added while stirring.

[0017] Furthermore, the pyrolysis time in step S3 and step S5 is 4 hours.

[0018] Furthermore, in step S3 and step S5, the heating rate is 10° C. / min.

[0019] Furthermore, in step S4, the mass fraction of the hydrofluoric acid solution is 5%; after the carbon carrier is soaked, it is washed with deionized water until the outlet water conductivity is 10 us / cm.

[0020] The beneficial effects of the present invention are:

[0021] (1) The present invention uses colloidal nano-silica as a template to prepare a mesoporous carbon carrier. Under the action of colloidal nano-silica and an activator, the pore structure of the prepared carbon carrier can be designed. A good pore structure can limit the size of platinum particles and control the particle size during the platinum particle loading process. At the same time, it has an inhibitory effect on the maturation of platinum particles during the use of fuel cells. At the same time, the use of hydrofluoric acid to remove the template is also relatively thorough, which can keep the impurity content of the carbon carrier at a low level.

[0022] (2) The present invention can significantly increase the stability of the carbon carrier after further graphitization. This will be more stable than traditional carbon carriers. In the harsh operating environment of high voltage and high acidity of fuel cells, carbon carriers with a high degree of graphitization will have better durability. At the same time, the improvement of the stability of the carbon carrier also reduces the generation of gases such as carbon monoxide and reduces the poisoning of platinum particles. This can further increase the service life of the fuel cell.

[0023] (3) The method of the present invention has relatively simple steps, fewer influencing factors to be controlled, and the performance of the samples prepared by the method of the present invention is stable. In addition, the preparation process of the method of the present invention does not contain toxic and harmful substances and is environmentally friendly. The present invention can be adapted to large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The voltammetric cycle curve of the platinum-carbon catalyst prepared by using the carbon support prepared in Example 1 of the present invention;

[0025] Figure 2 This is a TEM image of a platinum-carbon catalyst prepared using the carbon support prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] The present invention will be further described below in conjunction with the accompanying drawings. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to this embodiment.

[0027] Example 1

[0028] This embodiment provides a simple method for preparing a mesoporous carbon carrier for a fuel cell, comprising the following steps:

[0029] S1. Add 0.5 g of chitosan to 50 mL of 0.1 mol / L acetic acid solution, then add 1 g of colloidal SiO2 nanoparticles with a particle size of 5 nm and 0.4 g of zinc chloride while stirring to obtain a mixed solution.

[0030] S2. The mixed solution is heated to 50° C. and stirred to evaporate the solvent, and then dried at room temperature for 24 hours to obtain a translucent film.

[0031] S3, placing the translucent film in a tubular furnace, heating it to 900° C. at a heating rate of 10° C. / min in a nitrogen atmosphere, and pyrolyzing it at 900° C. for 4 h and then naturally cooling it to room temperature to obtain a carbon support;

[0032] S4. Soak the prepared carbon carrier in a 5% by mass hydrofluoric acid solution for 24 hours, and wash it with deionized water until the outlet water conductivity is 10 us / cm.

[0033] S5. Place the carbon carrier treated in step S4 in a graphitization furnace, heat it to 1600° C. at a heating rate of 10° C. / min under the protection of argon, and pyrolyze it at 1600° C. for 4 hours and then cool it naturally to room temperature to obtain a mesoporous carbon carrier for a fuel cell.

[0034] S6. Grind the mesoporous carbon carrier for fuel cells and pass it through a 200-mesh sieve.

[0035] Example 2

[0036] This embodiment provides a simple method for preparing a mesoporous carbon carrier for a fuel cell, comprising the following steps:

[0037] S1. Add 1.5 g agar to 50 mL of 0.1 mol / L nitric acid solution, and add 1 g of colloidal SiO2 nanoparticles with a particle size of 15 nm and 0.4 g of calcium carbonate while stirring.

[0038] S2. The above solution is heated to 50° C. and stirred to evaporate the solvent, and then dried at room temperature for 24 hours to obtain a translucent film.

[0039] S3, placing the translucent film in a tubular furnace, heating it to 900° C. at a heating rate of 10° C. / min in a nitrogen atmosphere, and pyrolyzing it at 900° C. for 4 h and then naturally cooling it to room temperature to obtain a carbon support;

[0040] S4. Soak the prepared carbon carrier in a 5% by mass hydrofluoric acid solution for 24 hours, and wash it with deionized water until the outlet water conductivity is 10 us / cm.

[0041] S5. Place the carbon carrier treated in step S4 in a graphitization furnace, heat it to 1600° C. at a heating rate of 10° C. / min under the protection of argon, and pyrolyze it at 1600° C. for 4 hours and then cool it naturally to room temperature to obtain a mesoporous carbon carrier for a fuel cell.

[0042] S6. Grind the mesoporous carbon carrier for fuel cells and pass it through a 200-mesh sieve.

[0043] Example 3

[0044] This embodiment provides a simple method for preparing a mesoporous carbon carrier for a fuel cell, comprising the following steps:

[0045] S1. Add 2.5 g agar to 50 mL of 0.1 mol / L acetic acid solution, and add 1 g of colloidal SiO2 nanoparticles with a particle size of 50 nm and 0.2 g of calcium chloride while stirring.

[0046] S2. The above solution is heated to 50° C. and stirred to evaporate the solvent, and then dried at room temperature for 24 hours to obtain a translucent film.

[0047] S3, placing the translucent film in a tubular furnace, heating it to 900° C. at a heating rate of 10° C. / min in a nitrogen atmosphere, and pyrolyzing it at 900° C. for 4 h and then naturally cooling it to room temperature to obtain a carbon support;

[0048] S4. Soak the prepared carbon carrier in a 5% by mass hydrofluoric acid solution for 24 hours, and wash it with deionized water until the outlet water conductivity is 10 us / cm.

[0049] S5. Place the carbon carrier treated in step S4 in a graphitization furnace, heat it to 1600° C. at a heating rate of 10° C. / min under the protection of argon, and pyrolyze it at 1600° C. for 4 hours and then cool it naturally to room temperature to obtain a mesoporous carbon carrier for a fuel cell.

[0050] S6. Grind the mesoporous carbon carrier for fuel cells and pass it through a 200-mesh sieve.

[0051] The carbon support prepared in the above example was used to prepare a platinum-carbon catalyst, and the prepared platinum-carbon catalyst was subjected to electrochemical testing to determine its electrochemical performance. The modification effect of the carbon support was then evaluated. The preparation process of the platinum-carbon catalyst is as follows:

[0052] Dissolve 2.2g of sodium citrate in 100g of ethylene glycol and ultrasonicate for 30min, then add 160.8g of chloroplatinic acid ethylene glycol solution. The concentration of chloroplatinic acid in the chloroplatinic acid ethylene glycol solution is 200mg / mL. Ultrasonicate the mixed solution for 30min and stir at 30℃ for 1h. Then add 2g of carbon carrier, ultrasonicate for 30min and stir at 30℃ for 1h. Dissolve 7.5g of sodium hydroxide in 100g of ethylene glycol solution, ultrasonicate for 30min and stir at 30℃ for 1h. Pour the reaction solution into a three-necked flask for reduction reaction. The reaction is carried out at 100℃, and the bottle mouth is condensed and refluxed. After the reaction is completed and cooled to room temperature, 50mL of 10wt% sulfuric acid solution is added to the solution. Stir the above solution for another 15min. Finally, the product is positively filtered with ultrapure water. After taking out the filter cake, add 800mL of ultrapure water to a 1L beaker and ultrasonicate for 30min before positive pressure filtration. Repeat the above operation until the conductivity of the filtrate is less than 1.0 us / cm. Take out the filter cake and place it in a 60°C forced air drying oven to dry overnight. Place the platinum carbon catalyst in a ball mill and grind it at low temperature for 2 hours and pass it through a 200-mesh standard sieve. A 60% Pt / C catalyst is obtained through the above experiment.

[0053] The electrochemical performance of the prepared platinum-carbon catalyst is shown in Table 1. Figure 1The voltammetric cycle curve of the platinum-carbon catalyst prepared from the carbon support of Example 1.

[0054] Table 1

[0055]

[0056] From the data in Table 1, the ECSA and MA performance data of the platinum-carbon catalyst prepared by using the carbon carrier prepared in Examples 1-3 to load the platinum particles are good. This shows that the carbon carrier plays a major role in improving the performance of the platinum-carbon catalyst. The design of the pore structure makes it easy to load the platinum particles. At the same time, the size of the pore size strictly limits the size of the platinum particles. Thereby achieving uniform size and uniform distribution of platinum particles. Its particle size meets the requirements of catalysis.

[0057] The average particle sizes of the platinum particles of the three platinum-carbon catalysts are shown in Table 2. Figure 2 Shown is a TEM image of a platinum-carbon catalyst prepared using the carbon support of Example 1.

[0058] Table 2

[0059]

[0060] As can be seen from Table 2, the platinum particle size of the platinum carbon catalyst prepared using the carbon carrier of Example 1 is better than that of Example 2 and Example 3. This is because the pore size of the carbon carrier of Example 1 is smaller than that of Example 2 and Example 3, thereby obtaining a better platinum particle size result. This also explains why the electrochemical activity, i.e., ECSA and MA, of the platinum carbon catalyst prepared using the carbon carrier of Example 1 is higher than that of Example 2 and Example 3. Reasonable pore size and reasonable pore distribution bring higher catalytic activity to the catalyst.

[0061] The specific surface area and pore size data of the carbon carriers finally prepared in Examples 1-3 are shown in Table 3.

[0062] Table 3

[0063]

[0064]

[0065] The test results of the specific surface area in Table 3 show that the specific surface area of ​​the carbon carrier of Example 1 is more suitable, and a larger specific surface area can provide more pores for the loading of platinum particles. At the same time, a smaller pore size can achieve the loading of smaller-sized platinum particles. According to the data in Table 2, it can be found that the particle size of the platinum particles of the platinum-carbon catalyst prepared using the carbon carrier of Example 1 is the best. A better particle size can obtain better catalytic activity, which is also mutually confirmed by the results of the electrochemical test.

[0066] For those skilled in the art, various corresponding changes and modifications can be made according to the above technical solutions and concepts, and all of these changes and modifications should be included in the protection scope of the claims of the present invention.

Claims

1. A simple method for preparing a mesoporous carbon carrier for a fuel cell, characterized in that: The following steps are involved: S1. Add polysaccharide to the acid solution, add colloidal SiO2 nanoparticles and activator while stirring, and finally obtain a mixed solution; S2, heating the mixed solution obtained in step S1 to 50° C. with stirring to evaporate the solvent and then drying at room temperature to obtain a translucent film; S3, placing the translucent film obtained in step S2 in a tube furnace, heating it to 900° C. in a nitrogen atmosphere, pyrolyzing it at 900° C., and then naturally cooling it to room temperature to obtain a carbon carrier; S4, soaking the carbon support obtained in step S3 with a hydrofluoric acid solution, and then washing with deionized water; S5. The cleaned carbon carrier obtained in step S4 is placed in a graphitization furnace, heated to 1600° C. under the protection of argon gas, and naturally cooled to room temperature after pyrolysis at 1600° C., thereby obtaining a mesoporous carbon carrier for a fuel cell.

2. The method according to claim 1, characterized in that In step S1, the acid solution includes one or more of nitric acid solution, sulfuric acid solution, acetic acid solution, perchloric acid solution, and hydrochloric acid solution.

3. The method according to claim 1, characterized in that In step S1, the polysaccharide is one or more of starch, cellulose, chitosan, polyfructose, and agar.

4. The method according to claim 1, characterized in that: In step S1, the activator includes one or more of zinc chloride, calcium chloride, calcium carbonate, potassium hydroxide, and sodium hydroxide.

5. The method according to claim 1, characterized in that In step S1, the particle size of the colloidal SiO2 nanoparticles is 5-50 nm.

6. The method according to claim 1, characterized in that In step S1, 0.5-2.5 g of polysaccharide is added to 50 mL of 0.1 mol / L acid solution, and 1 g of colloidal SiO2 nanoparticles and 0.2-0.4 g of activator are added while stirring.

7. The method according to claim 1, characterized in that The pyrolysis time in step S3 and step S5 is 4 hours.

8. The method according to claim 1, characterized in that: In step S3 and step S5, the heating rate is 10°C / min.

9. The method according to claim 1, characterized in that: In step S4, the mass fraction of the hydrofluoric acid solution is 5%; after the carbon carrier is soaked, it is washed with deionized water until the conductivity of the outlet water is 10 us / cm.